High-energy γ-ray detection of supernova remnants in the Large Magellanic Cloud. Issue 2 (6th July 2022) - Campana, R; Massaro, E; Bocchino, F; Miceli, M; Orlando, S; Tramacere, A
ABSTRACT: We present the results of a cluster search in the γ -ray sky images of the Large Magellanic Cloud (LMC) region by means of the Minimum Spanning Tree (MST) and DBSCAN algorithms, at energies higher than 6 and 10 GeV, using 12 yr of Fermi -LAT data. Several significant clusters were found, the majority of which associated with previously known γ -ray sources. We confirm our previous detection of the supernova remnants N 49B and N 63A and found new significant clusters associated with the SNRs N 49, N 186D, and N 44. These sources are among the brightest X-ray remnants in the LMC and corresponds to core-collapse supernovae interacting with dense H ii regions, indicating that a hadronic origin of high-energy photons is the most likely process.